DIGITAL FINANCIAL ASSETS: SEGMENTS AND PROSPECTS OF LEGAL REGULATION IN THE BRICS COUNTRIES - I. Sarnakov (BRICS Law Journal, 2019)
In the environment of the current trend towards digitalization of the world economy, the issue of the legal regulation of the institute of digital financial assets as well as the activity relating to the generation of these assets is of considerable interest. As practice shows, individual countries face the situation where these assets are already turning over, but there is still no legal regulation. This state of affairs may give rise to cases of illegal turnover of financial assets and fraud in this sphere. Presently, the geopolitical map on digitalization of the economy is fragmented. Some countries have recognized and legalized the turnover of digital financial assets, others have so far not adopted an unambiguous attitude with respect to this new institute, while a third group of countries has not even recognized their legal nature nor their very existence. This ambiguity raises many issues relating to the legitimacy of digital financial assets and the feasibility of the introduction of this new financial product. The article analyzes the state of the legal regulation of the institute of digital financial assets in the BRICS countries, considers the standpoints of legislators and scientists on the legal nature of these financial assets.